2021
DOI: 10.1038/s41467-020-20378-8
|View full text |Cite
|
Sign up to set email alerts
|

BRD4-mediated repression of p53 is a target for combination therapy in AML

Abstract: Acute myeloid leukemia (AML) is a typically lethal molecularly heterogeneous disease, with few broad-spectrum therapeutic targets. Unusually, most AML retain wild-type TP53, encoding the pro-apoptotic tumor suppressor p53. MDM2 inhibitors (MDM2i), which activate wild-type p53, and BET inhibitors (BETi), targeting the BET-family co-activator BRD4, both show encouraging pre-clinical activity, but limited clinical activity as single agents. Here, we report enhanced toxicity of combined MDM2i and BETi towards AML … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 52 publications
(96 reference statements)
2
44
0
Order By: Relevance
“…For example, MDM2 inhibitors or targeted agents that alter MDM2 activity/stability can augment chemotherapy response [210], be augmented by inhibitors of p53 inactivators such as WIP1 [234], or by inhibitors of IAPs [235], or direct activators of cell death such as BH3 mimetics [236]. Moreover, our work and others have shown that combinations with epigenetic modifying agents including HDACi [75] and bromodomain inhibitors [237] may enhance p53 induced cell death through more than one of these mechanisms and intriguingly, bispecific small molecules targeting MDM2 with BRD4, BCL2, and XIAP present interesting strategies for wild-type p53 containing tumours [238][239][240].…”
Section: Targeting P53 To Induce Cell Deathmentioning
confidence: 70%
“…For example, MDM2 inhibitors or targeted agents that alter MDM2 activity/stability can augment chemotherapy response [210], be augmented by inhibitors of p53 inactivators such as WIP1 [234], or by inhibitors of IAPs [235], or direct activators of cell death such as BH3 mimetics [236]. Moreover, our work and others have shown that combinations with epigenetic modifying agents including HDACi [75] and bromodomain inhibitors [237] may enhance p53 induced cell death through more than one of these mechanisms and intriguingly, bispecific small molecules targeting MDM2 with BRD4, BCL2, and XIAP present interesting strategies for wild-type p53 containing tumours [238][239][240].…”
Section: Targeting P53 To Induce Cell Deathmentioning
confidence: 70%
“…Furthermore, these post-MPN sAML cells show a higher sensitivity to PROTAC (proteolysis-targeting chimera) ARV-825 compared to normal hematopoietic stem and progenitor cells, enabling an important window of therapy [31]. Most recently, Latif et al reported enhanced toxicity of BETi and MDM2i in AML cells and in vivo mouse models [11]. The combination of BRD4 and MDM2 inhibition leads to an increase of p53 activation and its proapoptotic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Bromodomain and extraterminal domain (BET) family members represent one group of epigenetic modulators regulating gene transcription through recruitment of regulatory complexes to acetylated chromatin regions and interaction with RNA polymerase II [9]. The BET family member BRD4 was shown to regulate the transcription of important proto-oncogenes including MYC or BCL2 and mediates the repression of the tumor suppressor p53 [10,11]. BRD4 was identified as promising target structure in acute myeloid leukemia as inhibition of BRD4 using shRNA or a small molecule inhibitor resulted in anti-leukemic effects in vitro as well as in vivo [12].…”
Section: Introductionmentioning
confidence: 99%
“…Twenty years ago, the discovery of imatinib for the treatment of chronic myeloid leukemia and its remarkable activity raised hopes for similar benefits in targeted therapies for AML. Over the last few years, precision medicine has been proposed for several hematological malignancies including acute leukemia, and more than 100 different targets have been identified in AML, making it an optimal candidate for experimental clinical studies [ 18 , 19 , 20 , 21 , 22 ].…”
mentioning
confidence: 99%
“…More recently, a great number of experimental drugs targeting single metabolic pathways have been developed and tested in phase 1, 2 and 3 clinical trials [ 12 , 17 , 18 , 19 , 20 , 21 , 22 ]. The question remains: what is the main reason for using these agents in AML?…”
mentioning
confidence: 99%